The OECD MNE Guidelines: Recent complaints on emerging issues show the need to revise standards on responsible business conduct - Marian Ingrams; Thomas Mason; Joseph Wilde-Ramsing (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
The OECD Guidelines for MNEs should set the most up-to-date standards on responsible business conduct. By analyzing the issues emerging in complaints recently filed to the Guidelines' grievance mechanisms, this Perspective identifies substantive gaps in the standards and argues that the OECD should update the Guidelines in 2022.
Keywords: 330